Polyacetal Carboxylic Acids: a New Group of Antiviral Polyanions - Claes, P. (1970)
Chlorite-oxidized oxypolysaccharides are polyacetal carboxylic acids. They inhibited the cytopathic effect of vesicular stomatitis virus in mouse embryo cell cultures challenged at low input multiplicity. After intraperitoneal injection of these compounds in mice, interferon appeared in the circulation. The compounds also protected mice against lethal mengovirus infection and against the development of experimental pox lesions on the tail. Chlorite-oxidized oxyamylose was antiviral only when at least 64% of the glucopyranose units were oxidized, an observation which suggested a correlation between charge density and antiviral effect. The antiviral activity was also influenced by the molecular weight, as demonstrated by the fact that chlorite-oxidized dextrans which had a high intrinsic viscosity were more active than those with low intrinsic viscosity.